Democratisation Ignited from Below: Explaining Patterns of Democratisation from the Arab Spring - Gottfredsson,Stina (2020)
Since the mass protests erupted in early 2011 has the Arab Spring been the central focus for studies from various approaches. This study seeks to contribute to the understanding of the Arab Spring from the perspective of democratisation theory. More specifically, the study analyses the case of the Arab Spring as a set of paths determined by the interplay of class actors. In doing so, the study follows the strategy of comparative historical analysis. The case of comparison is the so-called Third wave of democratisation. Further, the analysis partly offers an empirical understanding of a set of cases representative of the Arab Spring which acts as the base of the comparison. Next, it also presents a theoretical discussion of the identified differences. Based on the analysis, the study argues that the interplay of working-class actors and elites continues to offer an explanation to paths towards democracy. More, it also highlights, compared to the historical wave, that the democratisation paths of the Arab Spring all ignited from a public demand from below.
Keywords: the Arab Spring; democratisation; democratic actors; labour movement; comparative historical analysis